RhoC regulates cancer stem cells in head and neck squamous cell carcinoma by overexpressing IL-6 and phosphorylation of STAT3. - Mozaffarul Islam; Smita Sharma; Theodoros N Teknos (PLoS ONE, 2014)
In this study we investigated the correlation between RhoC expression and cancer stem cells (CSCs) formation in head and neck squamous cell carcinoma (HNSCC). The inhibition of RhoC function was achieved using shRNA. The expression of stem cell surface markers, ALDH and CD44 were significantly low in two RhoC depleted HNSCC cell carcinoma cell lines. Furthermore, a striking reduction in tumorsphere formation was achieved in RhoC knockdown lines. The mRNA expression of RhoC in RhoC knockdown adherent and tumorspheres are dramatically down regulated as compared with the scrambled control. The mRNA expression of stem cell transcription factors; nanog, oct3/4 (Pouf1), and sox2 were significantly depleted in RhoC knockdown clones. Further, the phosphorylation of STAT3(ser727), and STAT3(tyr705) were significantly down regulated in RhoC knockdown clones. The overexpression of STAT3 in RhoC knockdown did not show any change in expression patterns of either-STAT3(tyr705) or stem cell transcription factors, signifying the role of RhoC in STAT3 activation and thus the expression of nanog, oct3/4 and sox2 in HNSCC. The expression of Inter leukin-6 (IL-6) in RhoC knockdown HNSCC cell lines was dramatically low as compared to the scrambled control. Further, we have shown a rescue in STAT3 phosphorylation by IL-6 stimulation in RhoC knockdown lines. This study is the first of its kind to establish the involvement of RhoC in STAT3 phosphorylation and hence in promoting the activation of core cancer stem cells (CSCs) transcription factors. These findings suggest that RhoC may be a novel target for HNSCC therapy.